METHODOLOGICAL APPROACH TO TOURISM, COLLECTIVE CAPACITIES AND PUBLIC POLICY NETWORKS IN SAN MATEO CAPULHUAC, MÉX. - Manjarrez Campos, Erika Fabiola (Benemérita Universidad Autónoma de Puebla, 2020)
The purpose of this article is to analyze the collective capacities that enable tourism in thecommunity of San Mateo Capulhuac, Mexico, based on variables and indicators that are part of amethodological approach proposal, which is highlighted as the main contribution, since whichallows to articulate with tourism the theoretical assumptions of collective capacities and publicpolicy networks. Since in the specialized literature the production that links both approaches withsuch activity is incipient, this collaboration is also intended to contribute for this gap. Derivedfrom the analysis, it was identified that although the different sectors have developed certaincapacities, they are insufficient to position tourism as a significant item in the community. However, the social sector has stood out as a head of tourism initiatives, which openspossibilities for action in other areas that support the precarious conditions of the inhabitants ofthat locality located in the State of Mexico.